Examination of operation specimens from patients with spinal tuberculosis for tubercle bacilli. Issue 6 (June 1983) - Allen, B W; Mitchison, D A; Darbyshire, J; Chew, W W; Gabriel, M
Abstract : Operation specimens from 52 Hong Kong patients considered to have tuberculosis of the spine were sent at -78 degrees C to London where they were cultured on two Löwenstein-Jensen medium slopes, a slope of 7H11 medium made selective with antibiotics and in two bottles of selective liquid Kirchner medium. Cultures of M tuberculosis, usually with only scanty colonies, were obtained from 37 of the patients. Pus and caseous matter yielded more positive cultures and more numerous colonies than other specimens, but eight of the 37 patients yielded positive cultures only from tissues lining abscess walls or from bone or intervertebral disc specimens. Cultures in Kirchner medium were never contaminated and twice as many were positive as cultures on the slopes; nine patients had cultures positive only on Kirchner medium. It is recommended that (i) a variety of operation specimens, always including pus or caseous material in volumes of at least 1 ml, should be sent for bacteriology; (ii) specimens should be cultured in selective Kirchner medium, with or without Löwenstein-Jensen slopes; (iii) cultures should be incubated for a minimum of 8-9 wk.